Réseaux et territorialité dans la Méditerranée occidentale au xie siècle - Travis Bruce (Mélanges de la Casa de Velázquez, 2010)
The Taifa kingdoms in the 11th century do not fit into modern notions of a territorial State.  Their leaders exercised political power over a given territory, but that territory lacked fixed frontiers, which evolved over time. In the absence of definite boundaries, these territories can be approached on the basis of their capacity to tax, a sign of political power at any given time. The territorial limits of the Taifa of Denia are especially difficult to identify in view of the fact that it was at once a mainland and a maritime power, and also fragmented. The Taifa was conceived as a number of components, an assemblage of networks and points whose territorial sway was marked as much by its ships as by its fortifications.  These features then suggest the need for a reassessment of the definition of territory and might even call into question the way that we define a State in a the context of mediaeval Islam.